2018
DOI: 10.1248/bpb.b18-00171
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Suppresses Tryptophan Catabolism in Human Colon Cancer Cells as Revealed by Metabolic Profiling and Targeted Metabolite Analysis

Abstract: Celastrol is well known for its anti-cancer effects, yet its specific mechanisms against colon cancer are still not fully elucidated. In this study, cytotoxic effect of celastrol against HCT116 colon cancer cells was investigated based on cell viability assay and flow cytometry assay, and the possible mechanism was explored using a strategy combining metabolic profiling and targeted metabolite analysis based on ultra performance liquid chromatography (UPLC)/MS. Celastrol was found to inhibit the growth of colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In the presence of ATP/dATP, Cytc, and apoptotic protease activator‐1 (Apaf‐1) form a polymer complex, which activates the precursor of Caspase‐9, leading to the activation of downstream effector Caspase‐3, and cutting the substrate to induce apoptosis . Numerous of evidence demonstrated that celastrol inhibit cancer cells proliferation through proapoptosis mechanism, including oral cancer, lung cancer, breast cancer, and colon cancer . In our study, western blotting and IF assays demonstrated that cleaved caspase‐3,9 were significantly increased when compared with the control groups, supporting that proapoptosis activity was induced after the celastrol treatment in CCA cells.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In the presence of ATP/dATP, Cytc, and apoptotic protease activator‐1 (Apaf‐1) form a polymer complex, which activates the precursor of Caspase‐9, leading to the activation of downstream effector Caspase‐3, and cutting the substrate to induce apoptosis . Numerous of evidence demonstrated that celastrol inhibit cancer cells proliferation through proapoptosis mechanism, including oral cancer, lung cancer, breast cancer, and colon cancer . In our study, western blotting and IF assays demonstrated that cleaved caspase‐3,9 were significantly increased when compared with the control groups, supporting that proapoptosis activity was induced after the celastrol treatment in CCA cells.…”
Section: Discussionmentioning
confidence: 46%
“…EMT is an important molecular mechanism of invasion and metastasis of malignant tumors . A large amount of evidence from experimental and clinical researches have highlight the important role of EMT in CCA metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Another active ingredient of H.Lév. Hutch, Cel suppresses tryptophan catabolism, shows its cytotoxic effect against colon cancer cells (Qi et al, 2018).…”
Section: The Relationship Between Amino Acid Metabolism and Toxicitymentioning
confidence: 99%
“…Colon cancer cells such as HT-29, Caco-2, and LC-180 cells harbor the entire enzyme machinery for tryptophan catabolism, whose rate is several folds higher than that in normal colon epithelium. 38 Qi et al 39 showed that the human colon cancer cells grown in vitro converted tryptophan to Kyn and that the treatment with anticancer agents suppressed the generation of Kyn and resulted in the accumulation of tryptophan within the cancer cells and its milieu. However, such studies performed in a two-dimensional cell culture may not accurately reflect the metabolism of tumors in a three-dimensional structure.…”
Section: Increase In Prothrombotic Metabolites In Cancermentioning
confidence: 99%